Peculiarities of social functioning of patients with post-schizophrenic depression - Stakhanov, Kirill (ScienceRise: Medical Science, 2017)
Aim of research – to determine disorders of the social functioning, typical for patients with PSD. Methods of research: The psychodiagnostic examination of patients included: HADS/HARS scale for the study of psychoemotional features of patients with post-schizophrenic depression; Bassa-Darki questionnaire. For studying socio-psychological features were used: the questionnaire of volitional self-control –VSC (Zverkov A.G., Eideman E.V.), questionnaire of the suicide risk (modified by T.N. Razuvaeva). The cognitive sphere was estimated using the methods “10 words” by A.R. Luria (1995), “Proof test” by B. Burdon (1995) and pictograms method. The study of the patients’ life quality was carried out using the method Mezzich, Coher, Ruipezer, Liu & Yoon, 1999. The statistical processing of obtained data and diagrams construction were realized using Excel programs and statistical package «Statistica 7.0. for Windows», and also using Student t-criterion, U-criterion of Mann-Whitney, Fisher j-criterion, Pearson c2-criterion. At the assessment of synchronicity, combination of changes of two variables or for the assessment of the similarity of two scale profiles, grade coefficients of correlations were calculated by Spearman and linear ones - by Pearson. In all cases of comparisons the probability of «р» divergences was determined. They were considered as statistically significant at p<0,05 Results. Within the research were studied data about the social functioning of patients with PSD. Mean points by scales of the volitional self-control questionnaire were low (G1 – 6,5 points, G2 – 6,8 points). Life quality indices were totally within the mean values diapason. Near a half of men and women with PSD had the bed or very bad level of adaptation (G1 – 67,65 %; G2 – 46,58 %), at that women were reliably less adapted comparing with men (р≤0,05). According to the assessment of studied persons, the level of the experienced social support was low, at that least indices related to the factor “social support from “important others” (G1 – 0,9 points; G2 – 0,6 points). In men and women with PSD was determined the high risk of realization of autoagressive tendencies. In men with PSD the risk of the suicidal behavior was most often connected with factors as “social pessimism” (5,9 points), “inability” (5,6 points), “temporal perspective” (5,5 points), “affection” (5,2 points). The suicidal behavior risk in women was less comparing with men that was testified by lower values on most scales of the questionnaire and also the higher index (comparing with G1) of the anti-suicidal factor (р≤0,05). The suicidal risk in women with PSD was mainly connected with factors as “demonstrativeness” (5,3 points) and “affection” (5,0 points). Conclusions. As a result to the realized research was revealed the decrease of the social functioning in patients with PSD, manifested in the lack of volitional self-control, bad level of adaptation, low level of the social support use. The decrease of the general life quality was registered in men and women with PSD. The important parameter, revealed within the research, is the high risk of autoagresive tendencies realization; they were reliably higher in men comparing with women (р≤0,05). The determined dysadaptive psychosocial characteristics are at the same time risk factors of disease relapses that must be taken into account at elaborating the system of the complex medical-psychological support for this category of patients